'A perfect-full harmonie': Pitch, tuning and instruments in the Elizabethan and Jacobean mixed consort. (6th June 2019) - Robinson, Richard
Abstract: Discussions of performance practice in Renaissance music are frequently characterized by the idea that problematic areas of enquiry may be resolved by more than one historically valid solution, thus meaning that a number of modern aesthetic preferences can theoretically be justified. The current article challenges this general notion via the specific example of the Elizabethan and Jacobean mixed consort (comprising lute, cittern, bandora, treble viol/violin, flute/recorder and bass viol). Although this ensemble has generated a large bibliography and discography over many decades of research, certain details still remain disputed, notably the probable pitch level(s) it used and also the size and tuning of each of its instruments, particularly the flute and recorder. In order to resolve these issues, this article considers the surviving mixed consort partbooks alongside relevant English evidence from c .1550 to 1630 found in written sources and iconographical depictions. Collectively, this suggests that, contrary to claims made by previous scholars, the mixed consort typically played at one general pitch level (irrespective of whether it accompanied singers or played alone) and that each of the six parts was primarily intended for one size and type of instrument only.